The 1998 SADC intervention in Lesotho: international law perspectives - Hilling, Alexander (Centre for Law and Society, 2026)
On the 22 September 1998 the South African National Defence Forces entered the Mountain Kingdom of Lesotho after the Prime Minister of Lesotho, Pakalitha Mosisili, filed a request for military assistance to the Southern African Development Community. Since the Second World War there have been numerous instances of troops being sent to another state allegedly upon invitation of the government. As in virtually all instances of military presence and action of one state's troops in another state's territory the question as to the legality of such a mission has to be dealt with against the background of contemporary public international law. During the East - West cold war and in the light of progressing decolonialization the world community became more and more sensitive about cross-border political influence and military action.